Solutions of shallow-water equations in non-rectangular cross-section channels - Thomas, Luis Pablo (2007)
Smooth solutions of the shallow-water equations for non-rectangular cross-sections channels are studied. It is found that a complete set of solutions can be classified in four Lie symmetry groups that show distinctive physical features.